Practicality sex education / Mohd Haziq Karem, Rozainah Hamiddon and Nurmashitah Rapa’ee - Karem, Mohd Haziq; Hamiddon, Rozainah; Rapa’ee, Nurmashitah (2011)
In the first chapter, it will consist the general view of our research in term of general background, research objective, significant of study, scope ant the limitations of study, problem statement, hypotheses and even definition of terms. Sex education is the process of acquiring information and forming attitudes and beliefs about sex, sexual identity, relationship and intimacy. Sex education is also about developing young people’s skills so that they make informal choices about their behaviour, and feel confident and competent about acting on their choices. It is widely accepted that young people have a right to sex education.